2012
DOI: 10.2174/1874325001206010250
|View full text |Cite
|
Sign up to set email alerts
|

Computerized Tomographic Morphometric Analysis of the Cervical Spine

Abstract: Background:Detailed knowledge of cervical canal and transverse foramens’ morphometry is critical for understanding the pathology of certain diseases and for proper preoperative planning. Lateral x-rays do not provide the necessary accuracy. A retrospective morphometric study of the cervical canal was performed at the authors’ institution to measure mean dimensions of sagittal canal diameter (SCD), right and left transverse foramens’ sagittal (SFD) and transverse (TFD) diameters and minimum distance between spi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
4
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 22 publications
3
25
4
3
Order By: Relevance
“…Although, the area of dens, which seems to be more relevant for screw design as well as stress distribution, is yet to be determined. Other studies focused more on the spinal canal parameters which play an important role in stenosis and itraspinal tumours diagnosis [14][15][16]. Some of the researches devoted themselves to measure the pedicle parameters for transpedicular crew fixation [8,[17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although, the area of dens, which seems to be more relevant for screw design as well as stress distribution, is yet to be determined. Other studies focused more on the spinal canal parameters which play an important role in stenosis and itraspinal tumours diagnosis [14][15][16]. Some of the researches devoted themselves to measure the pedicle parameters for transpedicular crew fixation [8,[17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Some of the researches devoted themselves to measure the pedicle parameters for transpedicular crew fixation [8,[17][18][19][20][21][22]. The previous studies obtained morphometric parameters either from CT scans or radiographs [10,16,17,23] or by direct measurement performed on cadavers [15,18,[24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…UlbriCH [14] noted a lowering from C1 to C6. Other studies [13] [15] noticed a fall from C1 to C4 with an increase to C5 and a decrease to C6. Our study as well as Singh et al [7] has not found any statistical significant difference between the APD1 of the cervical spinal canal of men and those of women.…”
Section: Discussionmentioning
confidence: 82%
“…Our study as well as Singh et al [7] has not found any statistical significant difference between the APD1 of the cervical spinal canal of men and those of women. However, Evangepolos et al [13] noticed a significant difference between the genders at C1. The comparison of the APD1 of our study with those of Singh et al [7] on the one hand and with those of Evangepolos et al [13] on the other hand, revealed that the differences are not statistically important.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation